2022
DOI: 10.1016/j.ekir.2022.01.1062
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Risk Factors and Outcomes of Kidney and Liver Cyst Infection in Kidney Transplant Recipient With ADPKD

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Repeated hospitalisation from recurrent cyst infections is an indication for nephrectomy, particularly in patients who are waiting to have an RT because of the risk of life-threatening sepsis post-transplantation in the setting of immunosuppression. 17 , 18 …”
Section: Management Of Complicationsmentioning
confidence: 99%
“…Repeated hospitalisation from recurrent cyst infections is an indication for nephrectomy, particularly in patients who are waiting to have an RT because of the risk of life-threatening sepsis post-transplantation in the setting of immunosuppression. 17 , 18 …”
Section: Management Of Complicationsmentioning
confidence: 99%
“…This raises the question about whether patients with ADPKD with a history of cyst infections may benefit from pretransplantation nephrectomy. In the study of Ronsin et al, 3 the risk to develop a new cyst infection in a patient with unilateral nephrectomy and a history of cyst infection was 9.1% versus 12.5% in a patient with a positive history for cyst infection, but without preemptive transplantation nephrectomy. This suggests that preemptive nephrectomy may only lead to a relatively small benefit to reduce the chance for a cyst infection.…”
mentioning
confidence: 96%
“…However, until recently, no data has been available to support this hypothesis. 2 Recently, KI Reports published a retrospective study of Ronsin et al 3 that investigated the incidence, risk factors and outcomes of cyst infections in transplanted patients with ADPKD. The authors found that though the incidence of cyst infection after kidney transplantation is low, history of cyst infection before transplantation represents the main risk factor.…”
mentioning
confidence: 99%
“…As they stated, prophylactic nephrectomy did not prevent cyst infection recurrence in the post-transplantation period in our retrospective cohort. 2 Among the 43 patients with a history of cyst infection, 11 had prophylactic unilateral nephrectomy (6 for recurrent cyst infection and 5 for insufficient place for renal allograft) and 32 patients did not receive pre-emptive transplantation nephrectomy. One (1 of 11, 9.1%) patient in the prophylactic unilateral nephrectomy group and 4 (4 of 32, 12.5%) in the group without prophylactic nephrectomy developed a cyst infection after kidney transplantation.…”
mentioning
confidence: 99%
“…Finally, cyst infection, also in a transplanted patient, is rarely life-threatening or even severe (1 of 12, 8% in the cyst infection determined by imaging) because their management in recent years has been improved with the use of lipophilic antibiotics for a long duration. 3 Therefore, balancing the surgical risk of prophylactic nephrectomy and the drawbacks mentioned above, do not plead for its implementation in all patients with a history of cyst infection but rather to confine it in the rare cases of frequently relapsing or persistent infection.…”
mentioning
confidence: 99%